2011
DOI: 10.1049/el.2011.0636
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength detection with integrated filter-less BiCMOS RGB sensor

Abstract: A filter-less BiCMOS RGB colour sensor for wavelength detection in the wavelength range from 400 to 900 nm is presented. The sensor is based on the effect that light with longer wavelength penetrates silicon deeper than light with shorter wavelength. The detector is formed by three vertically stacked photodiodes: a deep diode used as the sensing element for red light, a middle diode to detect green light and a shallow diode as the blue light detector. The resulting RGB output is used to accurately determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…The relatively low photo responsivity of the p‐n diode is because the SiNM is very thin. Low photoresponsivity and η EQE could be further improved by applying thicker SiNM or reflector layer on the plastic substrate 29, 30…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low photo responsivity of the p‐n diode is because the SiNM is very thin. Low photoresponsivity and η EQE could be further improved by applying thicker SiNM or reflector layer on the plastic substrate 29, 30…”
Section: Resultsmentioning
confidence: 99%
“…For 520nm light, we are mainly concerned with the rise and fall time of the photocurrent in the middle photodiode, even though all three pn junctions exhibit photogenerated current. Ideally, the bottom pn junction should not exhibit any response to green light, but fortunately the responsivity of the bottom pn junction is only half as large as the responsitivity of the middle pn junction for 520nm [4]. The rise and fall times of the photocurrent in the middle photodiode are 23.5 ns and 20.9 ns, leading to a maximum data rate of 30 Mbit/s.…”
Section: Measurement Results Of Transient Responsementioning
confidence: 99%
“…Then, a triple‐junction colour sensor fully compatible with CMOS technology was introduced [3]. A filter‐less multicolour photodetector using standard BiCMOS technology was reported [4]. With this structure, the colour detector achieved high compactness and the complexity of the chip was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…[11] As an important complement to above filter-assisted wavelength sensors, filterless sensor has lately received increasing research interest as well. [12][13][14] Although this device can quantitatively discriminate the wavelength of incident light, they are however characterized by relatively narrow sensing range and complicated device structures which entail very sophisticated instrument during device fabrication process. [15][16][17][18][19][20] Thereby, high-resolution wavelength sensor with simple device geometry is in great demand.Various study have shown that photodetectors composed of artificial nanostructures in the form of nanofilm or nanowires can exhibit unique optoelectronic characteristics.…”
mentioning
confidence: 99%